2013
DOI: 10.1093/aje/kws392
|View full text |Cite
|
Sign up to set email alerts
|

Positive Association Between Perfluoroalkyl Chemicals and Hyperuricemia in Children

Abstract: Hyperuricemia in children is associated with increased risk of high blood pressure, metabolic syndrome, and future cardiovascular disease. Serum perfluorooctanoic acid (PFOA) and perfluorooctane sulfonate (PFOS) levels have been shown to be positively associated with hyperuricemia in adults, but the association in children remains unexplored. We therefore examined the association between serum PFOA and PFOS levels and hyperuricemia in a representative sample of US children. A cross-sectional study was performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
42
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(47 citation statements)
references
References 42 publications
(53 reference statements)
5
42
0
Order By: Relevance
“…Another study found, however, a positive association with PFHxS [309]. PFOA and/or PFOS have been associated with serum uric acid [310,311], chronic kidney disease [312], abnormal liver enzyme increases, especially in obese individuals [313], cardiovascular disease [314] and thyroid disease [315]. Different PFAAs showed different, sex and ethnicity-dependent effects on thyroid [316].…”
Section: General Populationmentioning
confidence: 97%
See 1 more Smart Citation
“…Another study found, however, a positive association with PFHxS [309]. PFOA and/or PFOS have been associated with serum uric acid [310,311], chronic kidney disease [312], abnormal liver enzyme increases, especially in obese individuals [313], cardiovascular disease [314] and thyroid disease [315]. Different PFAAs showed different, sex and ethnicity-dependent effects on thyroid [316].…”
Section: General Populationmentioning
confidence: 97%
“…A "Navigation Guide" review of the available human and non-human evidence concluded similarly that developmental exposure to PFOA adversely affects fetal growth in mammals [333]. Serum PFOA and PFOS levels were positively associated with hyperuricemia [311] and dyslipidemia [223] in children and adolescents, even at the low exposure levels of the US general population.…”
Section: General Populationmentioning
confidence: 99%
“…15 Another study by Geiger et al confirmed the associations among children using nationally representative US data, showing an overall positive, significant association between both PFOA and PFOS, and total cholesterol and LDL-C. 16 Geiger et al also examined associations between PFCs and serum uric acid levels and results indicated a strong, significant relationship independent even after complex multivariate adjustment. 17 Finally, a cross-sectional study by Hoffman et al 18 found a modest association between PFOA (OR 1.12; 95% confidence interval [CI]: 1.01-1.23) and PFOS (OR 1.03; 95% CI: 1.01-1.05) and attention deficit hyperactivity disorder among children (n=571).…”
Section: Editorialmentioning
confidence: 97%
“…Such compounds are used as surfactants [17][18][19][20], agrochemicals [21,22], pharmaceutical [23][24][25][26][27], biological [28] and medical agents [29,30]. While they are detected in human bodies [31,32], municipal water and solid wastes in different industrial areas around the world [33][34][35] and considered as high polluter for environment and toxic compounds [36,37], perfluoroalkyl acids are interesting compounds used as tensioactifs [38][39][40], fire-fighting foam [41][42][43], fluoropolymers [44] and other important applications.…”
Section: Introductionmentioning
confidence: 99%